Über die Linie: E. Jünger and M. Heidegger Facing the Nihilism - Šerpytytė, Rita (Problemos, 2004)
This article focuses on determining the problem of nihilism in the philosophy of the 20th century. The author starts from the premises that the description of the phenomenon of nihilism faces the problem of the extension of the term of the nihilism itself – whether the “history” of nihilism coincides with the “history” of Nothingness. The question that is being analysed is if searching for the manifestations of the phenomenon of nihilism and its essential features one should treat nihilism as related to Nothingness. And this question concerns the ontological roots of the problem of nihilism. The target of the research is the famous discussion on nihilism between E. Jünger and M. Heidegger. What is being shown is that E. Jünger describes nihilism as the total technologization and the reduction of the world itself. Heidegger deconstructs Jünger's description and leads the discussion to the ontological perspective.
Keywords: nihilism; Nothingness; Being; technology; phenomenology; ontology.